Challenging Issues on Paranasal Sinuses - Wang, Tang-Chuan (IntechOpen, 2019)
Management of paranasal sinus disorders is not only a test of knowledge but it is also an art form. Great progress has been made on endoscopic sinus surgery in recent decades and this technique lets us look into the remote corners of sinuses. However, we still have a lot of challenging issues. The only way to solve these problems is to face them. Based on these concepts, this book incorporates new clinical and research developments as well as future perspectives in the ever-expanding field of rhinology. The book is a comprehensive reference for ENT residents and practicing otolaryngologists who wish to expand their expertise, develop a broader armamentarium of techniques, and successfully manage their patients with sinonasal disorders.